Pengaruh Model Pembelajaran Teknik Klarifikasi Nilai Dengan Setting Lesson Study Terhadap Sikap Sosial Dan Hasil Belajar Siswa - I Ketut Suparya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The result of analysis in this research are as follows: 1) there is difference of learning result and social attitude of students following the learning model of value clarification techniques with lesson study setting with conventional learning. 2) The result of the influence of learning model to the learning result obtained statistical value F = 14,372 with significance level <0,05. There significant differences from student learning outcomes that follow the learning with the model of learning value clarification techniques with lesson study settings compared with those following the conventional learning. 3) The result of analysis of the influence of learning model on social attitude obtained statistical value F = 8,918 with significance level <0,05. There is a significant difference of social attitudes of students who follow the learning with value clarification techniques learning model with lesson study setting compared to those following the conventional learning. Keywords: value clarification techniques; lesson study; social attitudes; learning outcomes